1967
DOI: 10.1042/bj1051275
|View full text |Cite
|
Sign up to set email alerts
|

Biliary excretion of foreign compounds. Biphenyl, stilboestrol and phenolphthalein in the rat: molecular weight, polarity and metabolism as factors in biliary excretion

Abstract: 1. The extent of biliary excretion of biphenyl, tetralin, stilboestrol and phenolphthalein was studied in the rat. 2. Biphenyl and its 4-hydroxy and 4,4'-dihydroxy derivatives are extensively excreted in the bile as glucuronides in amounts increasing in order of molecular weight. 3. Stilboestrol and its glucuronide are excreted almost quantitatively in the bile mainly as the monoglucuronide, as are also phenolphthalein and its glucuronide. 4. Tetralin is excreted to the extent of about 13% of the dose, mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(41 citation statements)
references
References 6 publications
(8 reference statements)
4
37
0
Order By: Relevance
“…The results obtained are considered in the light of the suggestions made in the preceding paper on the factors involved in biliary excretion. It is shown that most of the sulphonamides examined are poorly excreted in the bile and that this finding is in accord with the hypotheses elaborated by Millburn et al (1967).…”
supporting
confidence: 78%
“…The results obtained are considered in the light of the suggestions made in the preceding paper on the factors involved in biliary excretion. It is shown that most of the sulphonamides examined are poorly excreted in the bile and that this finding is in accord with the hypotheses elaborated by Millburn et al (1967).…”
supporting
confidence: 78%
“…These determinants are likely important for binding to transport proteins on the hepatocyte basolateral or canalicular membrane. A MW cutoff for biliary excretion was originally reported in the 1970s, with a MW threshold of 325±50 for rats and 500± 50 for humans (4,5). Based on the above threshold, it is expected that there is a higher chance for a compound with MW over 325 to undergo substantial biliary excretion (defined as >10% of the dose) in rats, while a higher MW is necessary in humans.…”
Section: Introductionmentioning
confidence: 99%
“…4. These results together with data from the literature suggest that the molecular weight at which the excretion of dications in the bile exceeds 10% of the dose is in the region of 500-600, which differs from the values for monocations (Hughes et al, 1973) and anions (Millburn et al, 1967;Hirom et al, 1972).…”
mentioning
confidence: 47%
“…4. These results together with data from the literature suggest that the molecular weight at which the excretion of dications in the bile exceeds 10% of the dose is in the region of 500-600, which differs from the values for monocations (Hughes et al, 1973) and anions (Millburn et al, 1967;Hirom et al, 1972).From a study of the biliary excretion in the rat, guinea pig and rabbit of some monoquaternary ammonium or pyridinium cations, Hughes et al (1973) suggested that there is a molecular-weight threshold of about 200±50 for the significant (i.e. 10% or more of the dose) biliary excretion of monoquaternary nitrogen cations in these species.…”
mentioning
confidence: 50%
See 1 more Smart Citation